Factors related to entrepreneurial incubation centers model verification through Delphi technique - Sahban, Muh. Amsal; Kumar M., Dileep; Sri Ramalu, Subramaniam (2013)
The students of business graduate program in many universities in Indonesia are undergoing frequent training programs to become entrepreneurs.The facilities provided by the universities are termed as business incubation program. Though many dimensions of incubation program are available through literature and various models which are adaptable to the Indonesian business school context has been less research into. A qualitative research is conducted to fix the dimension of a business incubation program among business graduates in Indonesia. In order to collect the data, the study followed interview, observation, focus group discussion and Delphi technique in this study.The study observed that there are seven factors which are closely associated with incubation programs such as space, sharedness, service, support, skill, seed capital and synergy.This paper provides an insight into an influential factor of business incubation programs for business graduate students in Indonesia.